Pulses for food and nutritional security: The technology perspective - Roy, Devesh; Kishore, Avinash; Joshi, P. K.; Mishra, B. (The Indian Journal of Genetics and Plant Breeding, 2017)
Pulses though extremely important from a food securityand nutrition perspective in India have lagged behindcereals and have been moved increasingly to marginalenvironments. The persistent demand supply gap in pulsesposes several challenges including technological ones thatstem from movement of pulses to difficult environmentsand its place in relation to the competing crops.Technologies in pulses have evolved in line with the needssuch as short duration to meet intercropping requirements.Given the long history of technology development thatlags behind principal crops marked by near absence ofprivate sector in R&D in pulses, it may be time to rethinkand try demand pull systems of research with AdvanceMarketing Commitments along the lines suggested forvaccines.